Advantages of Using 3D Numerical Models in Tunnel Design (Proceedings of Faculty of Civil Engineering, 2022)
The choice between 2D and 3D numerical modeling depends primarily on the subject analysis, project requirements, deadlines, available resources, as well as justification for additional investment in complex models. The results of 2D and 3D tunnel numerical models are presented in order to analyze the fundamental differences and to highlight the 3D model advantages. The models were created on the cross section with the largest overlay, all according to the design documentation. The analyses were performed using the RS2 and RS3 Rocscience programs. The obtained results have shown that the main advantage of the 3D model is the possibility to monitor the increase of radial displacements with excavation progress, and to provide a more realistic insight into the efficiency of the installed support elements.
Keywords: 3D numerical modeling; FEM; tunnels; rock support; convergence